2020
DOI: 10.1177/1471301220914751
|View full text |Cite
|
Sign up to set email alerts
|

Rotational care practices in minority ethnic families managing dementia: A qualitative study

Abstract: Background: Although minority ethnic families have a lower uptake of dementia care services, little research has explored how minority ethnic carers cope with and manage dementia care in their everyday lives. The aim of this study was to investigate organization of family dementia care in Turkish, Pakistani, and Arabic speaking minority ethnic families from the perspective of family carers, primary care dementia coordinators, and multicultural link workers in Denmark. Methods: Semi-structured qualitative indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 28 publications
2
38
0
Order By: Relevance
“…T. Nielsen et al, 2015;R. T. Nielsen et al, 2019;T. R. Nielsen et al, 2020), the participants stated that it was difficult to find the families who needed help.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T. Nielsen et al, 2015;R. T. Nielsen et al, 2019;T. R. Nielsen et al, 2020), the participants stated that it was difficult to find the families who needed help.…”
Section: Discussionmentioning
confidence: 99%
“…Language barriers, including a lack of available comprehensible information and difficulties in communicating with families and those suffering from dementia or cognitive impairment, are seen as major concerns (Kenning et al, 2017;Mukadam et al, 2011;Nielsen et al, 2019;Parveen et al, 2017;Sagbakken et al, 2018). Studies also point out that, due to cultural aspects, family caregivers from minority ethnic backgrounds may have different needs from and expectations of dementia healthcare service, suggesting a need to develop more culturally sensitive and appropriate pathways of care (Baghirathan et al, 2018;Chaouni & De Donder, 2018;Flaskerud, 2009;Mukadam et al, 2011;Nielsen et al, 2015Nielsen et al, , 2019Nielsen et al, , 2020Sagbakken et al, 2018).…”
Section: What Does This Paper Contribute To the Wider Global Clinical Community?mentioning
confidence: 99%
“…Importantly, the intervention can be delivered in the community setting using existing human resources and is tailored to the basic needs of family carers from minority ethnic groups providing care at home. Family carers from minority ethnic groups in Denmark often provide care at home with limited or no involvement of available community care services (Nielsen et al, 2019;Nielsen et al, 2020aNielsen et al, , 2020b. For them to provide the best care possible, appropriate and effective support is needed.…”
Section: Discussionmentioning
confidence: 99%
“…As pointed out by the facilitating multicultural workers in a post-program focus group meeting, the latter aspects may be particularly important in minority ethnic communities such as the Turkish, Pakistani and Arabic speaking as people with dementia and their family carers risk being isolated due to the high level of stigma attached to dementia and a lack of accessible culturally sensitive services. 10,[20][21][22] As well as raising awareness about dementia and knowledge about options for formal support, initiatives to provide a wider range of services that are tailored to the specific language and cultural needs of minority ethnic communities are needed. 4,23,24 The gender distribution, with only one male participating in the program sessions, can be explained by a general tendency for women being more worried about dementia, 25 more prepared to discuss sensitive issues concerning dementia care with peers, 26 and more likely to have the main responsibility for family dementia care, 27 also among families with minority ethnic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…4,8,9 However, several barriers in accessing services have been reported in minority ethnic communities in recent Danish and international studies, including difficulties navigating complex healthcare systems, language barriers, lack of culturally sensitive services, misconceptions and stigma, and different cultural values and norms for care. 4,6,8,10 Despite the growing evidence suggesting limited awareness of dementia in minority ethnic communities, initiatives aiming at increasing knowledge about dementia and available services in these communities have generally been sparse. Although there are local and national campaigns and educational programs to increase awareness and knowledge about dementia in Denmark, these rarely reach minority ethnic groups and it has been suggested that more proactive efforts that take language and cultural barriers into consideration may be needed to raise awareness of dementia and improve access to services.…”
Section: Introductionmentioning
confidence: 99%